2022
DOI: 10.1002/anie.202200763
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Electronic Metal‐Support Interactions in Single‐Atom Pt1−CuO Catalyst for Boosting Acetone Oxidation

Abstract: The development of highly active single-atom catalysts (SACs) and identifying their intrinsic active sites in oxidizing industrial hazardous hydrocarbons are challenging prospects. Tuning the electronic metal-support interactions (EMSIs) is valid for modulating the catalytic performance of SACs. We propose that the modulation of the EMSIs in a Pt 1 À CuO SAC significantly promotes the activity of the catalyst in acetone oxidation. The EMSIs promote charge redistribution through the unified PtÀ OÀ Cu moieties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…[21][22][23] In addition, a preliminary phenomenon is found that the catalytic activity of Pt supported on oxidized carbon supports is significantly better than that on unoxidized carbon supports. [24,25] In fact, it is known that Pt exhibits special affinity to O in many oxygen-containing metal supports, such as polyoxometalates and metal oxides (CuO, TiO 2 , Fe 2 O 3 , CeO 2 ), [26][27][28][29][30] which will bring about good catalytic activity due to metal-support interactions. In other words, Pt may be coordinated with oxygen-containing groups on supports to Atomic-scale utilization and coordination structure of Pt electrocatalyst is extremely crucial to decrease loading mass and maximize activity for hydrogen evolution reactions (HERs) and oxygen reduction reactions (ORRs).…”
mentioning
confidence: 99%
“…[21][22][23] In addition, a preliminary phenomenon is found that the catalytic activity of Pt supported on oxidized carbon supports is significantly better than that on unoxidized carbon supports. [24,25] In fact, it is known that Pt exhibits special affinity to O in many oxygen-containing metal supports, such as polyoxometalates and metal oxides (CuO, TiO 2 , Fe 2 O 3 , CeO 2 ), [26][27][28][29][30] which will bring about good catalytic activity due to metal-support interactions. In other words, Pt may be coordinated with oxygen-containing groups on supports to Atomic-scale utilization and coordination structure of Pt electrocatalyst is extremely crucial to decrease loading mass and maximize activity for hydrogen evolution reactions (HERs) and oxygen reduction reactions (ORRs).…”
mentioning
confidence: 99%
“…Besides, the surface of transition metals contains a large amount of hydroxide groups, hence providing suitable anchoring sites for the preparation of SACs to coordinate with metal atoms via M-O(OH) interactions. Recently, He et al 78…”
Section: Non-carbon-based Material-supported Fe-sacsmentioning
confidence: 99%
“…Besides, the surface of transition metals contains a large amount of hydroxide groups, hence providing suitable anchoring sites for the preparation of SACs to coordinate with metal atoms via M–O(OH) interactions. Recently, He et al 78 constructed single Pt atoms anchored on a CuO support by utilizing the electron transfer between Pt atoms and CuO. Zhang et al 79 synthesized atomically dispersed Pt on RuO 2 via an impregnation-adsorption method, which exhibited excellent catalytic activity for methanol oxidation under alkaline conditions.…”
Section: Synthesis Of Fe-sacs Using Different Support Materialsmentioning
confidence: 99%
“…Massive emission of chlorinated volatile organic compounds (CVOCs) from industrial manufacturing and municipal waste burning plays a vital role in ozone depletion and the formation of photochemical smog and haze. 1,2-Dichloroethane (1,2-DCE; a typical CVOC) widely used as an industrial solvent or an organic intermediate is highly concerned due to its environmental threat . Different technologies including photocatalysis, adsorption/absorption, non-thermal plasma treatment, catalytic destruction, and thermal incineration have been previously reported for CVOC elimination . Among which, the catalytic CVOC destruction is recognized as one of the most promising candidates and a benign process, attributing to its superior low-temperature activity, controllable reaction selectivity, and low energy consumption. , …”
Section: Introductionmentioning
confidence: 99%
“…4 Different technologies including photocatalysis, adsorption/absorption, non-thermal plasma treatment, catalytic destruction, and thermal incineration have been previously reported for CVOC elimination. 5 Among which, the catalytic CVOC destruction is recognized as one of the most promising candidates and a benign process, attributing to its superior low-temperature activity, controllable reaction selectivity, and low energy consumption. 6,7 Noble metal-based catalysts, transition metal oxides, and zeolites/modified zeolites have been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%